Analysis of Integrated Construction of Business and Finance in Datengxia Water Control Project - DENG Min; ZHANG Jing (Renmin Zhujiang)
The Datengxia Water Control Project is a grand construction,with huge investment,long-period construction,diversified sources of construction funds,and massive relevant interest groups.As the project construction is in full swing,original business and financial mechanisms have gradually restricted financial management's development towards a clear and systematic direction.To solve the problems existing in financial management,such as isolated business and financial process,rough engineering accounting,difficult and parallel implementation of two accounts,and high requirements of financial statement of completion in the central capital construction project,this paper achieves an integrated construction of business and finance under the framework of intelligent Datengxia,rebuilds the account set,and opens up the data flow of the project management system.Furthermore,it expands the integration and connectivity of multiple systems and all modules and presets the requirements of financial statement of completion in project construction,so as to gradually establish a smart financial management system.